Effect of Annealing Temperature on the Dynamic Characteristics of SS400 Steel Using Experimental Modal Analysis - Andiyanto Andiyanto; Baharudin Priwintoko (Akademi Inovasi Indonesia, 2025)
Heat treatment can alter the stiffness-related and energy-dissipation behaviour of structural steels, but its influence on the modal response of SS400 steel is still rarely reported using direct experimental modal testing. This study evaluates the effect of annealing temperature on the dynamic characteristics of SS400 steel specimens under free-free boundary conditions. Four specimen conditions were investigated: raw material and annealed specimens at 700 °C, 800 °C, and 900 °C. Each specimen had dimensions of 200 mm x 20 mm x 5 mm. Experimental modal analysis was conducted using an impact hammer with a fixed uniaxial accelerometer, six roving-hammer measurement points, 10 kHz sampling rate, H1 frequency response function, Hanning windowing, and PolyLSCF stabilization. The first two bending modes were identified. The first natural frequency decreased from 491.655 Hz in the raw material to 434.364 Hz after annealing at 900 °C, corresponding to an 11.65% reduction. The second natural frequency decreased from 1327.165 Hz to 1173.168 Hz, corresponding to an 11.60% reduction. Damping ratios also decreased with increasing annealing temperature, with the largest reduction observed at 900 °C. The results indicate that annealing temperature strongly affects the modal properties of SS400 steel, particularly by reducing frequency- and damping-related indicators at higher temperatures. The contribution of this work is the direct comparison of raw and annealed SS400 modal parameters using the same free-free impact-testing configuration, which provides a baseline modal-response dataset for vibration-sensitive SS400 applications.